2021
DOI: 10.3847/1538-4357/abddbd
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Pulsar XTE J1858+034: Discovery of the Cyclotron Line and the Revised Optical Identification

Abstract: We present the results of a detailed investigation of the poorly studied X-ray pulsar (XRP) XTE J1858+034 based on the data obtained with the NuSTAR observatory during the outburst of the source in 2019. The spectral analysis resulted in the discovery of a cyclotron absorption feature in the source spectrum at ∼48 keV in both the pulse phase-averaged and resolved spectra. Accurate X-ray localization of the source using the NuSTAR and Chandra observatories allowed us to accurately determine the position of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
4
6
0
Order By: Relevance
“…Using the XSPEC tool recorn, it was found that the absorption line parameters do not change significantly if the normalization of the background spectrum is increased by up to 50%, thus strengthening the interpretation of the absorption feature as real and not due to artifacts. The feature was also observed in phase-resolved spectra presented in the accompanying paper by Tsygankov et al (2021). Interpreting the feature at 48 keV as a CRSF and assuming a gravitational redshift of z g = 0.3 (for an NS mass and radius of 1.4 M e and 10 km, respectively), a magnetic field strength of B = (5.4 ± 0.1) × 10 12 G is obtained.…”
Section: Spectral Analysissupporting
confidence: 52%
See 2 more Smart Citations
“…Using the XSPEC tool recorn, it was found that the absorption line parameters do not change significantly if the normalization of the background spectrum is increased by up to 50%, thus strengthening the interpretation of the absorption feature as real and not due to artifacts. The feature was also observed in phase-resolved spectra presented in the accompanying paper by Tsygankov et al (2021). Interpreting the feature at 48 keV as a CRSF and assuming a gravitational redshift of z g = 0.3 (for an NS mass and radius of 1.4 M e and 10 km, respectively), a magnetic field strength of B = (5.4 ± 0.1) × 10 12 G is obtained.…”
Section: Spectral Analysissupporting
confidence: 52%
“…In addition, the Gaia counterpart is at an angular offset of 103″ from, and thus clearly not associated with, the optical counterpart proposed by Reig et al (2005). This question is discussed in more detail in the accompanying paper by Tsygankov et al (2021), who identified a counterpart based on Chandra and ground telescope observations with a probable distance of 7-14 kpc.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To estimate the extinction value in the direction to the IR-star and its distance, we used the method successively applied previously by Karasev et al (2015); Nabizadeh et al (2019); Tsygankov et al (2021); Salganik et al (2022) for different sources. By comparing the measured color of the source (𝐻 − 𝐾) 0.945 with intrinsic colors (𝐻 − 𝐾) 0 of various star classes Wegner (2000Wegner ( , 2006Wegner ( , 2007Wegner ( , 2014Wegner ( , 2015, we can estimate the corresponding reddening 𝐸 (𝐻 −𝐾) = (𝐻 −𝐾) − (𝐻 −𝐾) 0 and extinction 𝐴 𝐾 using a standard extinction law (Cardelli et al 1989), as Swift J1808.4−1754 is located far away from the Galactic bulge direction.…”
Section: Distance Estimationmentioning
confidence: 99%
“…The photogeometric distance (recommended by the authors as more accurate) to star #1 is 6.1 +2.0 −1.0 kpc and to star #2 is 8.7 +3.6 −5.1 kpc. To check how these values compare with the estimated star classes we investigated both stars using the method described and successively applied by Karasev et al (2015), Nabizadeh et al (2019), andTsygankov et al (2021). Taking the absolute values of stars of various classes in the and photometric filters from Wegner (2000Wegner ( , 2006Wegner ( , 2007Wegner ( , 2014Wegner ( , 2015 and applying corrections for the extinction and the distance, we determined at what distance they should be located and how strongly they should be extincted to match the observed magnitudes of the investigated companion in the and filters.…”
Section: Distance Estimationmentioning
confidence: 99%